-4a+5(a-6b+8)=

-4b-6(5a-5b)=

4(a+2b)+4(2b-5)=

(a+2b)(3a-2b)-3a²=


Odpowiedź :

-4a+5(a-6b+8)= -4a + 5a - 30b + 40 = a - 30b + 40

-4b-6(5a-5b)= -4b -30a + 30b = -30a + 26b

4(a+2b)+4(2b-5)= 4a + 8b + 8b - 20 = 4a + 16b -20

(a+2b)(3a-2b)-3a²= 3a² - 2ab +6ab -4b² - 3a² = 4ab -4b²
-4a+5a-30b+40=a-30b+40

26b-30a

4a+8b+8b-20=4a+16b-20

3a(kwadrat)-2ab+6ab-4b(kwadrat)-3a(kwadrat) =4ab -4b(kwadrat)
-4a+5(a-6b+8)=-4a+5a-30b+40=a-30b+40
-4b-6(5a-5b)=-4b-30a+30b=-30a+26b
4(a+2b)+4(2b-5)=4a+8b+8b-20=4a+16b+20
(a+2b)(3a-2b)-3a²=3a²-2ab+6ab-4b²=-4b²+4ab